Composition for composite brine completion fluid, composite brine completion fluid as well as preparation method and application of composite brine completion fluid

By using a specific proportion of compositions in the completion fluid, including formate, phosphate, etc., the existing completion fluid has poor stability, low density and strong corrosiveness under high temperature and high pressure conditions, and a completion fluid with high density, high temperature resistance, low corrosion and good reservoir protection performance is achieved.

CN119505833APending Publication Date: 2025-02-25CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411615071.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing completion fluid has poor settlement stability under high temperature and high pressure conditions, low density cannot be suitable for ultra-deep wells, and has strong corrosiveness, affecting reservoir protection.

Method used

The composition for composite brine completion fluid is used, including formate, phosphate, solubilizer, tackifier, cutter, corrosion inhibitor, oxygen deoxygenator and water, and is prepared by mixing in a specific proportion to form a completion fluid with high density, high temperature resistance, low corrosion and good reservoir protection properties.

Benefits of technology

It achieves long-term stability at high temperature, has high core permeability recovery value, and has excellent reservoir protection performance, which slows down the corrosiveness of the brine well fluid and the degradation trend of polymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131967980000121
    Figure BDA0005131967980000121
Patent Text Reader

Abstract

The invention relates to the field of well completion fluids, and discloses a composition for a composite brine well completion fluid, the composite brine well completion fluid, and a preparation method and application of the composite brine well completion fluid. The composition contains formate, phosphate, a solubilizer, a tackifier, a shear strength improving agent, a corrosion inhibitor, a deoxidant and water, and relative to 100 mL of water, the dosage of the formate is 100 g to 200 g, the dosage of the phosphate is 100 g to 200 g, the dosage of the solubilizer is 1 g to 4 g, the dosage of the tackifier is 2 g to 4 g, the dosage of the shear strength improving agent is 0.1 g to 0.5 g, the dosage of the corrosion inhibitor is 1 g to 2 g, and the dosage of the deoxidant is 1 g to 2 g. The dosage of the deoxidant is 0.1 g to 0.3 g. The composite brine completion fluid provided by the invention has the properties of high temperature resistance, low corrosion, high density and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of completion fluid, and in particular to a composite salt water completion fluid composition, a composite salt water completion fluid, and a preparation method and application thereof. Background Art

[0002] Completion fluid is a special liquid used in downhole engineering in oil and gas fields for various operations in the completion process, such as drilling, cementing and plugging. Completion fluid is usually made by mixing water or oil-based liquid with a series of additives.

[0003] At present, the commonly used completion fluid systems all have disadvantages. Among them, the drilling fluid-to-completion fluid system has poor sedimentation stability under high temperature and high pressure conditions; the salt water completion fluid system has low density and cannot be applied to ultra-deep wells; the solid phase components in the ultra-fine completion fluid system are easy to damage the reservoir and affect production capacity.

[0004] Luo Yufeng et al. (Luo Yufeng. Application of high-temperature resistant and high-density saturated brine drilling fluid in western Sichuan [J]. Drilling and Production Technology, 2017, 40(05): 98-101+7) developed a new completion fluid system with a density of 2.22 g / cm3 and a temperature resistance of 200°C. This system has the characteristics of high temperature and high salt resistance by adding fluid loss reducer, high temperature stabilizer and deoxidizer. At the same time, the synergistic effect of sodium sulfite and sodium chloride is used to greatly enhance the protection ability of oil and gas reservoirs. However, this system is expensive, has a high solid content, and has a low acid solubility, which is easy to cause reservoir damage.

[0005] Wu Ruoning et al. (Wu Ruoning, Xiong Hanqiao, Yue Chaoxian et al. New high-density clean composite brine completion fluid [J]. Drilling Fluids and Completion Fluids, 2018, 35(02): 138-142.) proposed an innovative formula for an economical high-density clean composite brine completion fluid. By cleverly using a solubilizer, they broke through the traditional density limit of inorganic salts calcium chloride and zinc chloride, and increased the density of the completion fluid to 1.926 g / cm without adding solid particles. 3 , while ensuring that the liquid remains stable in an environment of up to 140°C, but the system cannot be used in higher temperature environments.

[0006] In order to solve the problems existing in the above-mentioned prior art and meet the exploration and development of deep wells and ultra-deep wells (such as the Tarim Oilfield) in my country, it is urgent to develop a clean composite brine completion fluid system with high density, high temperature resistance, low corrosion and good reservoir protection performance. Summary of the invention

[0007] The purpose of the invention is to overcome the problems of low density, poor high temperature resistance and strong corrosiveness of the completion fluid in the prior art.

[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite salt water completion fluid composition, which contains formate, phosphate, solubilizer, viscosity enhancer, shear enhancer, corrosion inhibitor, deoxidizer and water;

[0009] The tackifier is composed of an acrylamide polymer and a hyperbranched polymer in a mass ratio of 0.5-3:1;

[0010] The number average molecular weight of the acrylamide polymer is 100,000-800,000;

[0011] In the hyperbranched polymer, the mass ratio of the structural unit provided by 2-acrylamido-2-methylpropanesulfonic acid to the structural unit provided by acrylamide is 1:0.8-1.31;

[0012] The pH value of the hyperbranched polymer is 8-10, and at 25° C., the apparent viscosity of a 1% aqueous solution is ≥20 mPa*s;

[0013] The solubilizer is selected from at least one of sodium dodecylbenzene sulfonate, glycerol and polyethylene glycol; relative to 100mL of the water, the amount of the formate is 100g-200g, the amount of the phosphate is 100g-200g, the amount of the solubilizer is 1g-4g, the amount of the viscosity enhancer is 2g-4g, the amount of the shear enhancer is 0.1g-0.5g, the amount of the corrosion inhibitor is 1g-2g, and the amount of the deoxidizer is 0.1g-0.3g.

[0014] The second aspect of the present invention provides a method for preparing a composite brine completion fluid, comprising contacting and mixing the components in a composite brine completion fluid composition to obtain the composite brine completion fluid;

[0015] The composite brine completion fluid composition is the composite brine completion fluid composition described in the first aspect above.

[0016] The third aspect of the present invention provides a composite brine completion fluid prepared by the method described in the second aspect.

[0017] The fourth aspect of the present invention provides the use of the composite salt water completion fluid described in the third aspect in oil testing and completion operations.

[0018] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:

[0019] (1) The composite brine completion fluid provided by the present invention has long-term stability at high temperature, high core permeability recovery value, and good reservoir protection performance.

[0020] (2) The composite brine completion fluid prepared by compounding specific thickeners, solubilizers and other substances in a certain proportion can reduce the corrosiveness of the brine well-killing fluid and the degradation trend of the polymer in a dissolved oxygen environment, and at the same time also has excellent properties such as high temperature resistance and high density. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] As mentioned above, the first aspect of the present invention provides a composite salt water completion fluid composition, which contains formate, phosphate, solubilizer, viscosity enhancer, shear enhancer, corrosion inhibitor, deoxidizer and water;

[0023] The tackifier is composed of an acrylamide polymer and a hyperbranched polymer in a mass ratio of 0.5-3:1;

[0024] The number average molecular weight of the acrylamide polymer is 100,000-800,000;

[0025] In the hyperbranched polymer, the mass ratio of the structural unit provided by 2-acrylamido-2-methylpropanesulfonic acid to the structural unit provided by acrylamide is 1:0.8-1.31;

[0026] The pH value of the hyperbranched polymer is 8-10, and at 25° C., the apparent viscosity of a 1% aqueous solution is ≥20 mPa*s;

[0027] The solubilizing agent is selected from at least one of sodium dodecylbenzene sulfonate, glycerol and polyethylene glycol;

[0028] Relative to 100mL of the water, the amount of the formate is 100g-200g, the amount of the phosphate is 100g-200g, the amount of the solubilizer is 1g-4g, the amount of the viscosity enhancer is 2g-4g, the amount of the shear enhancer is 0.1g-0.5g, the amount of the corrosion inhibitor is 1g-2g, and the amount of the deoxidizer is 0.1g-0.3g.

[0029] It should be noted that the 1% aqueous solution apparent viscosity mentioned in the present invention refers to the apparent viscosity of 1 g of the hyperbranched polymer in 100 g of water at 25°C.

[0030] Preferably, the viscosity enhancer is composed of an acrylamide polymer and a hyperbranched polymer in a mass ratio of 1-2:1.

[0031] Preferably, in the hyperbranched polymer, the mass ratio of the structural unit provided by 2-acrylamido-2-methylpropanesulfonic acid to the structural unit provided by acrylamide is 1:1.16-1.28.

[0032] The present invention has no special requirements for the preparation method of the hyperbranched polymer, and any preparation method known in the art can be used. According to a preferred embodiment, the present invention preferably uses the method disclosed in publication number CN113621107A to prepare the hyperbranched polymer.

[0033] Preferably, the formate is selected from at least one of sodium formate, potassium formate and cesium formate.

[0034] Preferably, the phosphate is selected from at least one of tripotassium phosphate, potassium pyrophosphate and dipotassium hydrogen phosphate.

[0035] More preferably, the phosphate is a combination of tripotassium phosphate and potassium pyrophosphate in a mass ratio of 1:0.8-1.2. The inventors of the present invention have found that in this preferred case, the composite brine completion fluid provided by the present invention has better corrosion resistance and a longer stable time at high temperature.

[0036] Preferably, the shearing agent is selected from at least one of sepiolite, attapulgite, lithium magnesium soapstone and nanofiber.

[0037] Preferably, the solubilizer is polyethylene glycol with a number average molecular weight of 200-400.

[0038] Preferably, the corrosion inhibitor is selected from at least one of benzotriazoles, organic amines and organic phosphonic acid polymers.

[0039] Preferably, the oxygen scavenger is at least one selected from sodium ascorbate, sodium bisulfite and sodium thiosulfate.

[0040] As mentioned above, the second aspect of the present invention provides a method for preparing a composite brine completion fluid, wherein the components in the composite brine completion fluid composition are contacted and mixed to obtain the composite brine completion fluid;

[0041] The composite brine completion fluid composition is the composite brine completion fluid composition described in the first aspect above.

[0042] In order to obtain a completion fluid with better high temperature stability and higher permeability recovery rate, according to a preferred embodiment, the contact mixing step includes:

[0043] (1) first stirring and mixing water and a solubilizing agent to obtain a mixture I;

[0044] (2) adding the hyperbranched polymer to the mixture I and stirring and mixing for a second time to obtain a mixture II;

[0045] (3) adding an acrylamide polymer to the mixture II and performing a third stirring mixing to obtain a mixture III;

[0046] (4) The mixture III is mixed with a shearing agent, a formate, a phosphate, a corrosion inhibitor, and an oxygen scavenger to obtain the composite brine completion fluid.

[0047] Preferably, in step (2) and step (3), the feeding rates of the hyperbranched polymer and the acrylamide polymer are independently ≤10 g / min relative to 1 L of the water.

[0048] Preferably, in step (1), the first stirring and mixing conditions include: a time of 5-10 min, and a stirring rate of ≥10000 rpm.

[0049] Preferably, in step (2) and step (3), the conditions for the second stirring and mixing and the third stirring and mixing independently include: a time of 5-10 min, and a stirring rate of ≥10000 rpm.

[0050] It should be noted that in step (2), the second stirring and mixing time does not include the time for adding the hyperbranched polymer and in step (3), the third stirring and mixing time does not include the time for adding the acrylamide polymer.

[0051] Preferably, in step (4), the fourth stirring and mixing conditions include: time of 20-60 min, stirring rate ≥10000 rpm.

[0052] According to a more preferred embodiment, in step (4), the method further comprises:

[0053] S1: mixing the cutting agent with the mixture III to obtain an intermediate product I;

[0054] S2: mixing the formate with the intermediate product I to obtain an intermediate product II;

[0055] S3: mixing the phosphate with the intermediate product II to obtain an intermediate product III;

[0056] S4: mixing the corrosion inhibitor with the intermediate product III to obtain an intermediate product IV;

[0057] S5: Mixing the deoxidizer with the intermediate product IV to obtain the composite brine completion fluid.

[0058] Preferably, the conditions of the mixing I, the mixing II, the mixing III, the mixing IV and the mixing V independently include: a time of 5-10 min, and a stirring rate of ≥10000 rpm.

[0059] It should be noted that in the method for preparing composite brine completion fluid provided by the present invention, there is no special requirement for the temperature in each step, and any temperature known in the art can be adopted. Exemplarily, the temperature in each step is independently 10-35°C.

[0060] As mentioned above, the third aspect of the present invention provides a composite brine completion fluid prepared by the method described in the second aspect.

[0061] As mentioned above, the fourth aspect of the present invention provides the use of the composite salt water completion fluid described in the third aspect in oil testing and completion operations.

[0062] The present invention will be described in detail below through examples. In the following examples, the instruments, reagents, materials, etc. involved, unless otherwise specified, are all conventional instruments, reagents, materials, etc. already in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. already in the prior art.

[0063] In the following examples, the raw materials, their property parameters and sources are as follows:

[0064] Solubilizer I: polyethylene glycol, number average molecular weight 400, purchased from Aladdin Company;

[0065] Solubilizer II: sodium dodecylbenzene sulfonate (linear), purchased from Aladdin Company;

[0066] Acrylamide polymer I: brand PF-polyVIS, number average molecular weight 200,000-500,000; purchased from China Oilfield Services Limited;

[0067] Vinyl polymer: HE100 polymer, purchased from Chevron Phillips Chemical Co., Ltd.;

[0068] Cutting agent: Sepiolite, purchased from Lingshou County Yuyuan Mineral Products Co., Ltd.;

[0069] Phosphate I is a combination of tripotassium phosphate and potassium pyrophosphate in a mass ratio of 1:1;

[0070] Corrosion inhibitor: brand LMH, benzotriazole, purchased from Chaoyang Guangda Chemical Company;

[0071] Deoxidizer: sodium thiosulfate, purchased from Aladdin Company;

[0072] Formate: Potassium formate, purchased from Bazhou Dade Petroleum Technology Co., Ltd.

[0073] The hyperbranched polymer was prepared according to the preparation method disclosed in CN 113621107A.

[0074] Preparation Example 1:

[0075] (a) 225 g of water was added to a reaction kettle, 61.6 g of 2-acrylamido-2-methylpropanesulfonic acid was added after stirring, potassium hydroxide was added to adjust the pH value of the system to 10.0, 50.72 g of acrylamide, 0.25 g of isobutyl xanthate, 0.0625 g of N,N-methylenebisacrylamide (branching agent), 0.25 g of potassium persulfate, and 1.8 g of Tween-80 emulsifier were added in sequence, and stirred until all dissolved to obtain an aqueous phase;

[0076] (b) adding 150 g of white oil and 16.2 g of Span-80 emulsifier into a reaction kettle, stirring until all of them are dissolved to obtain an oil phase;

[0077] (c) slowly adding the aqueous phase to the oil phase under stirring conditions, stirring for 20 minutes, and emulsifying at high speed (8000 r / min) for 20 minutes to obtain a monomer compound emulsion; placing the above emulsion in a constant temperature water bath at 35° C., passing nitrogen for 30 minutes, and reacting for 3 hours to obtain the first step hyperbranched polymer, adding the remaining amount of acrylamide and branching agent solution (12.68 mL of water + 12.68 g of acrylamide + 0.5625 g of branching agent) under stirring, and reacting at 35° C. under low speed stirring (2000 r / min) for 5 hours to obtain a hyperbranched polymer I.

[0078] The pH value of the hyperbranched polymer I is 8.72, and the apparent viscosity of a 1% aqueous solution is 21 mPa*s.

[0079] Preparation Example 2

[0080] Step (a) was carried out in accordance with the method of Preparation Example 1, except that the amount of acrylamide added was 59.136 g;

[0081] Step (b) is the same as in Preparation Example 1;

[0082] Step (c) was carried out in accordance with the method of Preparation Example 1, except that the amount of acrylamide added was 14.784 g; a hyperbranched polymer II was obtained.

[0083] The pH value of the hyperbranched polymer II is 9.10, and the apparent viscosity of a 1% aqueous solution is 20 mPa*s.

[0084] Comparative Preparation Example

[0085] Step (a) was carried out in accordance with the method of Preparation Example 1, except that the amount of acrylamide added was 68.992 g;

[0086] Step (b) is the same as in Preparation Example 1;

[0087] Step (c) was carried out in accordance with the method of Preparation Example 1, except that the amount of acrylamide added was 17.248 g; hyperbranched polymer DI was obtained.

[0088] The pH value of the hyperbranched polymer II is 8.01, and the apparent viscosity of a 1% aqueous solution is 19 mPa*s.

[0089] Example 1

[0090] (1) first stirring and mixing water and a solubilizing agent to obtain a mixture I;

[0091] (2) adding the hyperbranched polymer to the mixture I and stirring and mixing for a second time to obtain a mixture II;

[0092] (3) adding the acrylamide polymer to the mixture II and performing a third stirring mixing to obtain a mixture III;

[0093] (4) mixing the cutting agent with the mixture III to obtain an intermediate product I;

[0094] (5) mixing the formate with the intermediate product I to obtain an intermediate product II;

[0095] (6) mixing the phosphate with the intermediate product II to obtain an intermediate product III;

[0096] (7) mixing the corrosion inhibitor with the intermediate product III to obtain an intermediate product IV;

[0097] (8) The deoxidizer is mixed with the intermediate product IV to obtain a composite brine completion fluid.

[0098] In this embodiment, the temperature of stirring and mixing is 25° C.; the conditions of mixing I, mixing II, mixing III, mixing IV and mixing V are all: time is 5 min, and the stirring rate is 12000 rpm.

[0099] The types, amounts and other process parameters of the substances involved in this example are listed in Table 1.

[0100] Unless otherwise specified, the remaining examples are carried out in accordance with the method of Example 1, except that the raw materials and process parameters used in each example are different, as shown in Table 1 for details.

[0101] Table 1

[0102] Example 1 Example 2 Water dosage / mL 100 100 Types of solubilizers Solubilizer I Solubilizer I Dosage / g 4 2 First stir to mix Time / min 5 10 Stirring speed / rpm 12000 10000 Types of hyperbranched polymers Hyperbranched polymer II Hyperbranched polymer II Dosage / g 1 1 Feed rate of hyperbranched polymer g / min 1 0.8 Second stirring mix Time / min 5 10 Stirring speed / rpm 12000 10000 Types of acrylamide polymers Acrylamide polymer I Acrylamide polymer I Dosage / g 2 1 Feeding rate of acrylamide polymer g / min 1 0.8 Third stirring Time / min 5 10 Stirring speed / rpm 12000 10000 Cutting agent / g 0.5 0.3 Formate / g 200 150 Types of phosphates Phosphate I Phosphate I Dosage / g 200 150 Corrosion inhibitor / g 2 1.5 Deoxidizer / g 0.3 0.2

[0103] Example 3

[0104] This example is carried out in a similar manner to that of Example 1, except that in this example, an equal mass of hyperbranched polymer I is used to replace the hyperbranched polymer II in Example 1 to obtain a composite brine completion fluid.

[0105] Example 4

[0106] This example is carried out in a similar manner to that of Example 1, except that the amount of the hyperbranched polymer II in this example is adjusted to 0.85 g, and the amount of the acrylamide polymer I is adjusted to 2.15 g, to obtain a composite brine completion fluid.

[0107] Example 5

[0108] This example is carried out in a similar manner to that of Example 1, except that in this example, an equal mass of solubilizer II is used to replace the solubilizer I in Example 1 to obtain a composite brine completion fluid.

[0109] Example 6

[0110] Step (1) is the same as in Example 1;

[0111] (2) adding the acrylamide polymer to the mixture I and stirring and mixing for a second time to obtain a mixture II; the conditions for the second stirring and mixing are the same as those in Example 1;

[0112] (3) adding the hyperbranched polymer to the mixture II for a third stirring and mixing to obtain a mixture III; the conditions for the third stirring and mixing are the same as those in Example 1;

[0113] Step (4), step (5), step (6), step (7) and step (8) are the same as in Example 1 to obtain a composite brine completion fluid.

[0114] The specific types, amounts and feeding rates of the acrylamide polymer and the hyperbranched polymer are the same as those in Example 1.

[0115] Comparative Example 1

[0116] This comparative example was carried out in a similar manner to Example 1, except that in this comparative example, an equal mass of hyperbranched polymer DI was used to replace the hyperbranched polymer II in Example 1 to obtain a composite brine completion fluid.

[0117] Comparative Example 2

[0118] This comparative example was carried out in a similar manner to Example 1, except that the amount of the hyperbranched polymer II in this comparative example was adjusted to 0.6 g, and the amount of the acrylamide polymer I was adjusted to 2.4 g, to obtain a composite brine completion fluid.

[0119] Comparative Example 3

[0120] This comparative example was carried out in a similar manner to Example 1, except that the amount of the hyperbranched polymer II in this comparative example was adjusted to 1.5 g, and the amount of the acrylamide polymer I was adjusted to 3 g, to obtain a composite brine completion fluid.

[0121] Comparative Example 4

[0122] This comparative example was carried out in a similar manner to Example 1, except that an equal mass of vinyl polymer was used to replace the acrylamide polymer in Example 1 to obtain a composite brine completion fluid.

[0123] Test Case

[0124] The composite brine completion fluid obtained in the above examples was subjected to the following performance evaluations: pH value determination, density determination, compatibility test, long-term high-temperature stability test, corrosion evaluation test, and reservoir protection evaluation test. The specific results are shown in Table 2.

[0125] pH value determination: pH value of composite brine completion fluid was determined using a pH meter.

[0126] Density test: Use a densitometer to measure the density of the composite brine completion fluid.

[0127] Long-term high-temperature stability experiment: Referring to the determination method of rheological properties of oil and gas well drilling fluids, the ZNN-D 6 six-speed rotary viscometer was used to determine the viscosity and shear properties of the completion fluid before aging. The completion fluid was then canned and placed at 180°C for aging for 1d, 3d, 5d, 7d, 10d, 13d, and 15d to test the changes in the viscosity and shear properties of the completion fluid under different aging times.

[0128] Corrosion evaluation experiment: The test was conducted in accordance with GB / T 6461-2002 "Corrosion test methods for metals and alloys". Specifically, the corrosion rate was determined using the hanging plate method. The material of the experimental steel sheet was P110. The experimental conditions were: temperature 180°C and the experimental time was 3 days.

[0129] Permeability recovery rate test method:

[0130] (1) Measure core length, diameter, mass, porosity and other parameters.

[0131] (2) Testing the initial permeability of the core: applying a confining pressure of 4.5 MPa to the core, and positively driving the core with a 2 wt % KCl solution. After the permeability is stable, the experimental data of the initial permeability K1 of the core is recorded.

[0132] (3) Testing the permeability of the core after damage: switch the valve, pump in the completion fluid obtained in the example for reverse drive, stop the pump after the fluid output from the outlet is stable, switch the valve, and drive forward with 2 wt% KCl solution to obtain the permeability K2 of the core;

[0133] (4) Calculate the core permeability recovery rate: the formula is: K2 / K1*100%.

[0134] Table 2

[0135]

[0136] It can be seen from the results in Table 2 that the composite brine completion fluid provided by the present invention has good solubility, high density, long stability time at high temperature, low corrosion rate, and high core permeability recovery value after being damaged by the clean brine well-killing fluid.

[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite brine completion fluid composition, characterized in that: The composition contains formates, phosphates, solubilizers, viscosity enhancers, shear enhancers, corrosion inhibitors, deoxidizers and water; The tackifier is composed of an acrylamide polymer and a hyperbranched polymer in a mass ratio of 0.5-3:1; The number average molecular weight of the acrylamide polymer is 100,000-800,000; In the hyperbranched polymer, the mass ratio of the structural unit provided by 2-acrylamido-2-methylpropanesulfonic acid to the structural unit provided by acrylamide is 1:0.8-1.31; The pH value of the hyperbranched polymer is 8-10, and at 25° C., the apparent viscosity of a 1% aqueous solution is ≥20 mPa*s; The solubilizing agent is selected from at least one of sodium dodecylbenzene sulfonate, glycerol and polyethylene glycol; Relative to 100mL of the water, the amount of the formate is 100g-200g, the amount of the phosphate is 100g-200g, the amount of the solubilizer is 1g-4g, the amount of the viscosity enhancer is 2g-4g, the amount of the shear enhancer is 0.1g-0.5g, the amount of the corrosion inhibitor is 1g-2g, and the amount of the deoxidizer is 0.1g-0.3g.

2. The composition according to claim 1, characterized in that The tackifier is composed of an acrylamide polymer and a hyperbranched polymer in a mass ratio of 1-2:

1.

3. The composition according to claim 1 or 2, characterized in that In the hyperbranched polymer, the mass ratio of the structural unit provided by 2-acrylamido-2-methylpropanesulfonic acid to the structural unit provided by acrylamide is 1:1.16-1.

28.

4. The composition according to claim 1 or 2, characterized in that The formate is selected from at least one of sodium formate, potassium formate and cesium formate; And / or, the phosphate is selected from at least one of tripotassium phosphate, potassium pyrophosphate and dipotassium hydrogen phosphate; And / or, the cutting agent is selected from at least one of sepiolite, attapulgite, lithium magnesium soapstone and nanofiber; And / or, the solubilizing agent is polyethylene glycol having a number average molecular weight of 200-400; Preferably, the phosphate is a combination of tripotassium phosphate and potassium pyrophosphate in a mass ratio of 1:0.8-1.

2.

5. A method for preparing a composite brine completion fluid, characterized in that: Contacting and mixing the components in the composite salt water completion fluid composition to obtain the composite salt water completion fluid; The composite brine completion fluid composition is the composite brine completion fluid composition according to any one of claims 1 to 4.

6. The method according to claim 5, characterized in that The contact mixing step comprises: (1) first stirring and mixing water and a solubilizing agent to obtain a mixture I; (2) adding the hyperbranched polymer to the mixture I and stirring and mixing for a second time to obtain a mixture II; (3) adding an acrylamide polymer to the mixture II and performing a third stirring mixing to obtain a mixture III; (4) The mixture III is mixed with a shearing agent, a formate, a phosphate, a corrosion inhibitor, and an oxygen scavenger to obtain the composite brine completion fluid.

7. The method according to claim 6, characterized in that In step (2) and step (3), the feeding rates of the hyperbranched polymer and the acrylamide polymer are independently ≤10 g / min relative to 1 L of the water.

8. The method according to claim 6 or 7, in step (2) and step (3), the conditions for the second stirring and mixing and the third stirring and mixing independently include: The stirring time is 5-10 minutes and the stirring rate is ≥10000rpm.

9. The composite brine completion fluid prepared by the method according to any one of claims 5 to 8.

10. Use of the composite salt water completion fluid according to claim 9 in oil testing and completion operations.

Citation Information

Patent Citations

  • High-temperature-resistant high-density formate polysulfonate drilling fluid and preparation method thereof

    CN102766446A

  • Strong-inhibition low-corrosion brine completion fluid capable of replacing CaBr2, and preparation method thereof

    CN106928943A

  • Long-acting stable formate well completion fluid as well as preparation method and application thereof

    CN111154462A

  • Inverse emulsion hyperbranched polymer filtrate reducer for drilling fluid as well as preparation method and application thereof

    CN113621107A

  • Low-corrosion solid-free high-density completion fluid and preparation method thereof

    CN114836191A